2016
DOI: 10.3233/wor-162331
|View full text |Cite
|
Sign up to set email alerts
|

The Work-It Study for people with arthritis: Study protocol and baseline sample characteristics

Abstract: Abstract. BACKGROUND:People with arthritis are at risk of work disability. Job accommodation and educational programs delivered before imminent work loss can minimize work disability, yet are not currently being widely implemented. The Work-It Study is a randomized controlled trial testing the efficacy of a problem solving program delivered by physical and occupational therapy practitioners to prevent work loss over a two-year period among people with arthritis and rheumatological conditions. OBJECTIVE: The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Four published and two ongoing studies were identified. [29][30][31][32][33][34] Of the four completed studies, all were conducted in 2005 or earlier. While the completed studies included individuals with SLE, SLE was not necessarily the primary focus; of the 979 participants across the four studies, only 9% had SLE, as each study primarily involved patients with rheumatoid arthritis or osteoarthritis.…”
Section: Hacking For Slementioning
confidence: 99%
“…Four published and two ongoing studies were identified. [29][30][31][32][33][34] Of the four completed studies, all were conducted in 2005 or earlier. While the completed studies included individuals with SLE, SLE was not necessarily the primary focus; of the 979 participants across the four studies, only 9% had SLE, as each study primarily involved patients with rheumatoid arthritis or osteoarthritis.…”
Section: Hacking For Slementioning
confidence: 99%
“…The “Work It” Study is a randomized controlled trial of people with self-reported arthritis or related rheumatic conditions at risk of work loss. The detailed methods of the trial protocol and findings are published elsewhere [ 18 , 19 ]. This clinical trial was approved by the Institutional Review Board for Boston University, and all participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…The “Work it” study is a clinical trial designed to test the efficacy of a work barrier identification and problem-solving educational program on reducing work limitations (16). Participants were people who self-reported arthritis and a concern about their ability to continue working for the next few years due to their health conditions.…”
Section: Methodsmentioning
confidence: 99%